2015
DOI: 10.1002/adfm.201502440
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Electronic Properties of Crystalline, Isomerically Pure Anthradithiophene Derivatives

Abstract: considering that the majority of devices based on ADTs reported to date have been formed from a material consisting of a mixture of isomers. Typically, isomeric mixtures are expected to offer decreased electronic performance, due to the inhomogeneities in intermolecular order that arise in the crystalline state. [ 6 ] The isomer mixtures ( mix ADTs) arise due to the nonregiospecifi c aldol condensation used in the most common synthesis of the ADT chromophore. [ 7 ] Even in the case of highly soluble ADT deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 37 publications
2
46
0
Order By: Relevance
“…[18] A more recent study focused on ADT derivatives also reported a higher field-effect mobility, µ, in the pure anti -isomer, and found that both types of pure isomer devices outperformed the mix -isomer sample. [19] That publication reports µ values of 2.0, 2.2, and 4.7 cm 2 V −1 s −1 for OFET devices of the mix -, syn -, and anti -isomers, of 2,8-difluoro-5,11-bis(triethylsilylethynyl) anthradithiophene (diF-TES ADT) and 2.3, 2.7, and 6.2 cm 2 V −1 s −1 in 2,8-difluoro-5,11-bis(triethylgermylethynyl) anthradithiophene (diF-TEG ADT). In addition, research into other 1D and 2D aromatic molecules, as well as polymers of isomeric monomers, indicate a general disparity in performance between isomers of the same compound.…”
Section: Introductionmentioning
confidence: 99%
“…[18] A more recent study focused on ADT derivatives also reported a higher field-effect mobility, µ, in the pure anti -isomer, and found that both types of pure isomer devices outperformed the mix -isomer sample. [19] That publication reports µ values of 2.0, 2.2, and 4.7 cm 2 V −1 s −1 for OFET devices of the mix -, syn -, and anti -isomers, of 2,8-difluoro-5,11-bis(triethylsilylethynyl) anthradithiophene (diF-TES ADT) and 2.3, 2.7, and 6.2 cm 2 V −1 s −1 in 2,8-difluoro-5,11-bis(triethylgermylethynyl) anthradithiophene (diF-TEG ADT). In addition, research into other 1D and 2D aromatic molecules, as well as polymers of isomeric monomers, indicate a general disparity in performance between isomers of the same compound.…”
Section: Introductionmentioning
confidence: 99%
“…For molecules with low degrees of symmetry, adjacent molecules can pack in a disordered manner despite the molecules being isomerically equivalent. For isomerically pure ADTs, the anti isomer shows the lowest degree of thiophene positional disorder in the experimental crystal structures, 146,149 which could lead to more homogenous charge-carrier transport pathways and offers a plausible explanation for the larger hole mobilities determined from transistor studies.…”
Section: Azapentacenes and Benzodithiophene As Model Systems To Invesmentioning
confidence: 99%
“…From a materials design standpoint, it is important to realize that the substitution of thiophene into an acene structure can lead to an isomeric mixture of products. 146,[148][149][150] In addition to isomeric purity, molecular symmetry can play a role. For molecules with low degrees of symmetry, adjacent molecules can pack in a disordered manner despite the molecules being isomerically equivalent.…”
Section: Azapentacenes and Benzodithiophene As Model Systems To Invesmentioning
confidence: 99%
See 2 more Smart Citations